DAERAH PENANGKAPAN MEMANCING REKREASI DI KOTA BANDA ACEH - Nafis Huwaidi; Faisal Syahputra; Agus Naufal (JURNAL KREASI RAKYAT, 2025)
Indonesia, as the largest archipelagic country in the world, possesses abundant fisheries resources, including along the coastal areas of Banda Aceh City. Recreational fishing has become an integral part of local culture while also contributing significantly to the local economy. This study aims to identify strategic recreational fishing locations, the types of bait used, and the composition of fish caught by anglers in the region. The research was conducted from April to May 2025 using a purposive sampling method, with data collected from six key fishing spots: Alue Naga Beach, Syiah Kuala Beach, Lampulo Beach, Kampung Jawa Beach, Ulee Lheue Beach, and Krueng Neng River. Data collection methods included direct observation, interviews with recreational fishers, and field documentation. The results show that the most commonly used bait was fresh shrimp due to its availability and high effectiveness in attracting various fish species. Dominant fish species caught included Baby GT (Caranx ignobilis), Snapper (Lutjanus spp.), Grouper (Epinephelus spp.), Tompel (Selaroides leptolepis), and Kerong (Leiognathus spp.). Beyond its recreational value, fishing activities have also created economic opportunities for local communities through the sale of bait, fishing gear, and food products. This study recommends the development of eco-based recreational fishing tourism to support environmental conservation while enhancing local economic welfare.